RECOUNTING AS REALIZATION OF BROWN AND LEVINSON’S POSITIVE POLITENESS STRATEGIES IN INSTRUCTIONAL INTERACTIONS - Pramujiono, Agung (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2019)
Abstract: In instructional interactions, a lecturer should be able to build harmony in a conducive classroom atmosphere in order that a learning objective can be attained. This study aims to describe recounting as the realization of Brown and Levinson's positive politeness strategies in instructional interactions in the classroom. The subjects of this study were six lecturers from the Satya Wacana Christian University Salatiga. The research data were in the form of lecturer utterances when lecturing. The data were collected using the participant observation. The data analysis was performed using descriptive techniques following the Miles and Huberman flow model. Based on the results of data analysis, it revealed that the recounts employed included ones about lecturers, students, lecturers' experiences, and public figures/attitudes of public figures.  These findings can be used to strengthen and revise the positive politeness sub-strategies of Brown and Levinson (1987). In addition to functioning to forge a close relationship with interactants, the recounting strategy also serves to instill character values and to motivate. students to be more disciplined, and to optimize their own potential of becoming creative students. The use of recount as a positive politeness substrategy has contributed to efforts to create humanistic-based learning.Keyword: storytelling, positive politeness strategies, instructional interactionsAbstrak: Dalam interaksi instruksional, seorang dosen dituntut mampu membangun harmoni di kelas sehingga terbangun suasana kelas yang kondusif sehingga tujuan pembelajaran dapat tercapai. Penelitian ini bertujuan mendeskripsikan bercerita sebagai realisasi strategi kesantunan positif Brown dan Levinson dalam interaksi instruksional di kelas. Subjek penelitian ini adalah enam orang dosen Universitas Kristen Satya Wacana Salatiga. Data penelitian berupa ujaran dosen dalam perkuliahan.  Data dikumpulkan dengan menggunakan metode simak dengan teknik rekam dan wawancara mendalam. Analisis data dilakukan dengan menggunakan teknik deskriptif mengikuti model alir Miles dan Huberman. Berdasarkan hasil analisis data ditemukan cerita yang digunakan meliputi cerita tentang diri dosen, cerita tentang mahasiswa, cerita tentang pengalaman dosen, dan cerita tentang tokoh/sikap tokoh. Selain berfungsi membangun kedekatan hubungan dengan interaktan, strategi bercerita juga berfungsi untuk menanamkan nilai karakter dan untuk memotivasi mahasiswa.Kata Kunci: bercerita, strategi kesantunan positif, interaksi instruksional